Author Reply: Illuminating the Health Benefits of Psychological Assets. (January 2018) - Hernandez, Rosalba; Bassett, Sarah M.; Schuette, Stephanie A.; Shiu, Eva W.; Moskowitz, Judith T.
This reply addresses observations of Drs. Larsen, Kruse, and Sweeny, and Scherer in their reviews of our published work on the link between positive psychological assets and outcomes of physical health. Inspired by Obama's Precision Medicine Initiative we argue that the interplay between the emotion spectrum and health is likely a complex and heterogeneous amalgam of known and yet unidentified elements melding at the individual level. When exploring the emotion–health link, researchers are challenged to grapple with complex system models by considering multiple hierarchies of information that span individual-level factors, genetic blueprints, and cultural and environmental context. Research is needed to more fully elucidate the mechanism through which emotion influences health, with careful consideration of differences across race/ethnicity, culture, and context.